The Relationships Between Density of Mangroves and Sediment Organic Content with Macroepifauna Abundance in Anak Setatah Village, District of Meranti Archipelago - Erick Palatema; Bintal Amin; Efriyeldi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The research was conducted in December 2015 in Anak Setatah Village, District of Meranti Archipelago. This research aimed to analyze the density of mangrove, sediment organic content, abundance of macroepifauna, relationships between density of mangrove and organic content in sediment with macroepifauna abundance. Mangrove density measurements was done using 10 x 10 m² observation plots, whilst sampling of macroepifauna using 5 x 5 m² plot with two replication at each plot. The results of the research showed that water quality parameters measured were still in the range of water quality criteria for marine organisms. Density of mangrove in Station 1 was 2,283.33 ind/ha and in Station 2 was 1,283.33 ind/ha. The sediment organic content in Station 1 was 15.10 % and Station 2 was 15.50 %. The macroepifauna abundance in Station 1 was 4,600 ind/ha and Station 2 was 1,200 ind/ha. Non significant posititive correlation between sediment organic content and macroepifauna abundance was found which shown by regression equation in Station 1 y = 2966,8 + 72,851x, R2 = 0,002, r = 0.04 and Station 2 y = 483.1 + 20.435x, R2 = 0.0007, r = 0.026. Non significant postitive correlation between mangrove density and macroepifauna abundance was also found and shown by regression equation y = 1266.5 + 0.3081x, R² = 0.105 r = 0.324 (Station 1) and y = 503.27 + 0.2312x, R2 = 0.0108, r = 0.103 (Station 2).Key Word: mangrove, organic, sediment, macroepifauna